A year of programs for millennials and more - Alessio, Amy J.; LaMantia, Katie; Vinci, Emily, 1988- (ALA Editions, An imprint of the American Library Association, 2015)
A collection of programming ideas, with a target audience from late teens to millennials into their forties. Includes suggestions for marketing the programs, and examines the needs and takeaway goals for each program. Programs are arranged through the calendar year.